Perlindungan Hukum Terhadap Anak sebagai Korban Tindak Pidana Pencabulan dan Persetubuhan - Udin Nurkholis Huda; Hartoyo Hartoyo; Fitri Ayuningtyas (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The crime of molestation and sexual intercourse against children is an act that violates social norms of politeness, religion and decency. Article 28b paragraph (2) of the 1945 Constitution of the Republic of Indonesia reads: "Every child has the right to survival, growth, and development and has the right to protection from violence and discrimination" The legal issue of this normative legal research: How is the criminal act of molestation and sexual intercourse against children regulated? What is the form of legal protection for children as victims of sexual acts and sexual intercourse? The crime of molestation is regulated in Articles 289 to 295 of the Criminal Code, Law No. 35 of 2014: It is an amendment to Law No. 23 of 2002 concerning Child Protection, which affirms the prohibition of violence or threats against children (Article 76E) and establishes prison sanctions of between 5 to 15 years for perpetrators (Article 82) and Law No. 12 of 2022 concerning the Crime of Sexual Violence. The form of legal protection for children as victims of criminal acts of molestation and sexual intercourse is Physical and Psychological Protection, Victims' children have the right to physical protection to ensure safety from the threat of the perpetrator, through the arrest of the perpetrator with sufficient preliminary evidence. Psychological protection is provided with rehabilitation, counseling, and psychosocial assistance during the legal process until recovery. 2. Confidentiality of the identity of the victim; 3. Legal and Social Assistance; 4. Restitution and Restoration of Rights; 5. Strict Law Enforcement.